KONSEP KEWENANGAN SEBAGAI LANDASAN FORMULASI HUKUMAN TINDAK PIDANA KORUPSI - Marah Halim (Universitas Islam Negeri Ar-Raniry, 2014)
Although the Corruption Act has been specific, but its punishment system not constructed from its basic concept, that is the concept of authority. As a result, a lot of things that are paradoxical and contradictory in its substance; particularly in the construction of its criminal elements. This study departs from the belief that this problem will be solved if the system is reconstructed with reference to the concept of punishment authority as its